2020
DOI: 10.1186/s13071-020-04397-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic, proteomic and phenotypic studies of Leishmania donovani strains revealed genetic features associated with virulence and antimony-resistance

Abstract: Background Leishmaniasis is a neglected tropical disease affecting millions of people worldwide. Emerging drug resistance of Leishmania species poses threaten to the effective control and elimination programme of this neglected tropical disease. Methods In this work, we conducted drug-resistance testing, whole genome resequencing and proteome profiling for a recently reported clinical isolate with supposed drug resistance (HCZ), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
1
7
1
Order By: Relevance
“…Variations in the parasite genome can be associated with its geographical distribution and clinical manifestations, which can influence leishmaniasis management. Interestingly, large-scale research involving a large number of samples and wide geographic range has revealed that genetic diversity is significantly higher than that previously reported ( Bussotti et al., 2018 ; Zackay et al., 2018 ; Franssen et al., 2020 ; Imamura et al., 2020 ; Patino et al., 2020 ; Salloum et al., 2020 ; Zheng et al., 2020 ; Patino et al., 2021 ; Schwabl et al., 2021 ). Recently, single-cell sequencing has demonstrated the presence of several distinct karyotypes within the same Leishmania clone ( Imamura et al., 2020 ; Negreira et al., 2020 ), and multiple-genotype infections have been demonstrated to occur even within the same host and tissue ( Cupolillo et al., 2020 ).…”
Section: Importance Of Genetic Diversity and Genome Plasticity Of Leishmaniacontrasting
confidence: 58%
“…Variations in the parasite genome can be associated with its geographical distribution and clinical manifestations, which can influence leishmaniasis management. Interestingly, large-scale research involving a large number of samples and wide geographic range has revealed that genetic diversity is significantly higher than that previously reported ( Bussotti et al., 2018 ; Zackay et al., 2018 ; Franssen et al., 2020 ; Imamura et al., 2020 ; Patino et al., 2020 ; Salloum et al., 2020 ; Zheng et al., 2020 ; Patino et al., 2021 ; Schwabl et al., 2021 ). Recently, single-cell sequencing has demonstrated the presence of several distinct karyotypes within the same Leishmania clone ( Imamura et al., 2020 ; Negreira et al., 2020 ), and multiple-genotype infections have been demonstrated to occur even within the same host and tissue ( Cupolillo et al., 2020 ).…”
Section: Importance Of Genetic Diversity and Genome Plasticity Of Leishmaniacontrasting
confidence: 58%
“…Otherwise, there are evidences to suggest that a non-inhibition of the fatty acid βoxidation is associated with an antimony-resistant profile. Not only genetic variations but also a predominant upregulation in proteins involved in fatty acid β-oxidation have been described in antimony resistant parasites [22,58,59]. Particularly, the long-chain fatty acyl-CoA ligase (LCFA) a key enzyme involved in β-oxidation of long fatty acids has been found to be differentially increased in antimony-resistant Leishmania donovani amastigotes by microarray analysis [60,61].…”
Section: The Changes In Lipid Composition Allow the Differentiation Of Antimony Resistant Phenotypes By Multivariate Analysismentioning
confidence: 99%
“…According to these two papers, some interesting results attracted our attention. In this study, we found the genes of protein kinase, kinesin, amastin-like surface protein, N-acyl-L-amino acid amidohydrolase protein and sodium stibogluconate resistance protein in L_HCZ had more mutations, and in our previous study we found the expression of these genes at the protein level was up-regulated [65]. Similarly, the mutation of mitogen-activated protein kinase in L_HCZ was less than that in L_9044 and L_Liu, and the protein expressed by this gene was down-regulated.…”
Section: Discussionmentioning
confidence: 51%
“…The datasets of the five Leishmania clinical isolates will provide a molecular basis for future research on the pathogenic mechanism, drug resistance mechanism and vaccine development of Leishmania. In our previous study, we focused on verifying the virulence and antimony resistance of the Leishmania clinical isolate (L_HCZ) at molecular levels and proved that L_HCZ has high-level pathogenicity and evident antimony resistance in vitro, using an integrative approach of genome sequencing, proteomic profiling and phenotypic analysis to find the target spot of virulence and antimony resistance of L_HCZ [65]. According to these two papers, some interesting results attracted our attention.…”
Section: Discussionmentioning
confidence: 99%